KUALITAS FISIK WAFER TANAMAN JAGUNG DAN GAMAL DENGAN VARIASI KOMPOSISI DAN LAMA WAKTU PENGEPRESAN - Nyimas Popi Indriani; Nisa Sakiila Arsadianti; Yang Halimah Nur.Azizah; Vita Dwicahyani; Romi Zamhir Islami; Mansyur Mansyur (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
This research aimed to evaluate wafers from corn plant and Gamal compositions and the pressing times on wafer quality, namely water content, specific gravity, density, and wafer absorption capacity. The research was experimental using a completely randomized design and factorial pattern (2×3) with 6 replications. Factor A was the composition of corn and Gamal. A1; Corn (70%) and Gamal (30%) and A2; Corn (80%) and Gamal (20%). Factor B was the pressing time, B1 to B3 for 15, 20, and 25 minutes pressing times respectively. Physical quality variabls were analyzed through ANOVA also Duncan's advanced test. The water content and specific gravity were not different (P>0.05), while density and water absorption were different (P<0.05). There was an interaction between composition and pressing time. Water content ranged from 10.48-12.77% and average specific gravity ranged from 1.00-1.18% g/ml. The density of A1B3 (0.565 g/cm3) had a water absorption capacity of 86.835%. The best result was corn plants (70%) and Gamal (30%) and pressing time for 25 minutes.